Prevalence of Chronic Diseases and Alterations of Gut Microbiome in People of Ningxia China During Urbanization: An Epidemiological Survey - Du, Yong; Ding, Lu; Na, Li; Sun, Ting; Sun, Xian; Wang, Liqun; He, Shulan; Wang, Zhizhong; Lu, Zhenhui; Li, Feng; Guo, Xiaofei; Zhang, Yanhong; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
The continuous development of urbanization has dramatically changed people's living environment and lifestyle, accompanied by the increased prevalence of chronic diseases. However, there is little research on the effect of urbanization on gut microbiome in residents. Here we investigated the relation between living environment and gut microbiota in a homogenous population along an urban-rural gradient in Ningxia China. According to the degree of urbanization, the population is divided into four groups: mountainous rural (MR) represents non-urbanized areas, mountainous urban (MU) and plain rural (PR) represent preliminary urbanization, and plain urban (PU) is a representative of complete urbanization. Studies have found that with the deepening of urbanization, the prevalence of chronic diseases, such as diabetes, dyslipidemia, fatty liver, gallstones, and renal cysts, have gradually increased. The intestinal richness and diversity of the microbial community were significantly reduced in the PR and the PU groups compared with the MR and the MU groups. Based on linear discriminant analysis selection, the significantly enriched genera Faecalibacterium, Prevotella, and Pseudobutyrivibrio in the MR group gradually decreased in the MU, the PR, and the PU groups. Effect size results revealed that both residence and diet had an effect on intestinal microbiota. Our results suggested that the disparate patterns of gut microbiota composition were revealed at different levels of urbanization, providing an opportunity to understand the pathogenesis of chronic diseases and the contribution of the “rural microbiome” in potential protection against the occurrence of chronic diseases.